Electronic health record usage among nurse practitioners, physician assistants, and junior residents. Issue 3 (29th March 2021) - Watson, Michael D.; Elhage, Sharbel A.; Scully, Casey; Peterson, Sabrina; Gulledge, Marialice; Cunningham, Kyle; Sachdev, Gaurav
ABSTRACT: Background: Studies demonstrate significant electronic health record (EHR) use by junior residents; however, few studies have investigated this for nurse practitioners and physician assistants (NPs/PAs). Purpose: The aim of this study was to quantify the time spent on the EHR by NPs/PAs and junior residents. Methods: Electronic health record usage data were collected from April 2015 through April 2016. Monthly EHR usage was compared between NPs/PAs and postgraduate second and third year residents. Further subgroup analysis of NPs/PAs and residents from surgical or nonsurgical fields was conducted. Results: Data for 22 NPs/PAs (16 surgical and six nonsurgical) and 125 residents (31 surgical and 94 nonsurgical) were analyzed. Nurse practitioners/physician assistants opened fewer charts per day (4.9 ± 1.5 vs. 5.4 ± 3.1), placed more orders per month, and spent more daily time on the EHR (176.5 ± 51.7 minutes vs. 152.3 ± 71.9 minutes; p < .0001). Compared with residents, NPs/PAs spent more time per patient in all categories (chart review, documentation, order entry) and in total time per patient chart (all p < .05). Comparing surgical NPs/PAs to surgical residents, findings were similar with fewer charts per day, more total daily EHR time, and more EHR time per patient in every tracked category (all p < .05). Implications for practice: This is the first study to quantify time on the EHR for NPs/PAs. Nurse practitioners/physician assistants spent more time on the EHR than residents, and this is accentuated with surgical NPs/PAs. Electronic health record utilization appears more burdensome for NPs/PAs; however, the reason for this is unclear and highlights the need for targeted interventions.